GaN high electron mobility transistors on silicon substrates with MBE/PVD AlN seed layers. Issue 3 (19th March 2014) - Cordier, Y.; Frayssinet, E.; Chmielowska, M.; Nemoz, M.; Courville, A.; Vennéguès, P.; Mierry, P. De; Chenot, S.; Camus, J.; Aissa, K. Ait; Simon, Q.; Brizoual, L. Le; et al.
Abstract: In the present paper, we describe the development of new AlN seed layers obtained by combining molecular beam epitaxy and low temperature physical vapour deposition (magnetron sputtering). It is shown that it is possible to grow thick AlN seed layers with a good in‐plane crystal ordering. GaN based structures on silicon can then be regrown with device quality active layers, as attested by the realization of high electron mobility transistors. Furthermore, the low substrate bowing achieved with these structures is of high interest for the fabrication of large GaN‐on‐silicon wafers. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)